Reference standards for accurate validation and optimization of assays that determine integrated lentiviral vector copy number in transduced cells - Paugh, Barbara S. (Sci Rep, 2021)
Lentiviral vectors (LV) have emerged as a robust technology for therapeutic gene delivery into human cells as advanced medicinal products. As these products are increasingly commercialized, there are concomitant demands for their characterization to ensure safety, efficacy and consistency. Standards are essential for accurately measuring parameters for such product characterization. A critical parameter is the vector copy number (VCN) which measures the genetic dose of a transgene present in gene-modified cells. Here we describe a set of clonal Jurkat cell lines with defined copy numbers of a reference lentiviral vector integrated into their genomes. Genomic DNA was characterized for copy number, genomic integrity and integration coordinates and showed uniform performance across independent quantitative PCR assays. Stability studies during continuous long-term culture demonstrated sustained renewability of the reference standard source material. DNA from the Jurkat VCN standards would be useful for control of quantitative PCR assays for VCN determination in LV gene-modified cellular products and clinical samples.